Development of e-module to enhance online learning amongst UiTM distance learners - Jamaludin, Haziah; Hamzah, Suzana; Ramli, Mohd Ismail (2012)
UiTM Centre of Online Education has been providing its students with the printed Self Instructional Materials (SIM) by popular demand as students find it convenient to have printed materials to refer to. Nonetheless, being virtual learners, having e module is most fitting to their mode of learning because online engagements can encourage students to frequent virtual classroom, thus, increasing online participation. The study seeks ways on the possibilities to adapt the printed SIMs in the development of eSIM. It has the following objectives: 1. To analyse the present Self Instructional Materials 2. To develop 3 electronic modules which support the online learning The analysis of printed SIM was carried on two broad area of content and presentation which was further devided into smaller factors namely updateability, relevance, concreteness, connectedness, interactivity, stimulating, navigation, motivation and attention. Data for the analysis was collected through a survey on 200 students and interview with 5 subject matter experts and experienced instructional designers. This analysis serve two purposes; an evaluation of the exixting SIM and a need analysis for the development of eSIM. Findings show that more than 70% of the respondents are satisfied with the presentation of the information and the content in the printed SIM. However, they prefer to have more graphical information and would like to have additional examples and exercises. Thus, the new e-SIMs are designed with enhanced presentation, more exercises with feedbacks and video of skill demonstration. While the print based materials can still contribute to achieving the learning outcomes, the web based learning can support learning in terms of interactivity, hyperlinks, motivation and attention.